Genome-wide association mapping in hairy vetch (Vicia villosa) discovers a large effect locus controlling seed dormancy - Tilhou, Neal; Kucek, Lisa Kissing; Carr, Brandon; Marion, Annie; Douglas, Joel; Englert, John; Ali, Shahjahan; Raasch, John; Bhamidimarri, Suresh; Mirsky, Steven Brian; Monteros, Maria J.; Krogman, Sarah; et al. (Frontiers in Plant Science, 2023)
Hairy vetch (Vicia villosa Roth), a winter hardy annual legume, is a promising cover crop. To fully leverage its potential, seed production and field performance of V. villosa must be improved to facilitate producer adoption. Two classic domestication traits, seed dormancy (hard seed) and dehiscence (pod shatter), are selection targets in an ongoing breeding program. This study reports a genome-wide association study of 1,019 V. villosa individuals evaluated at two sites (Knox City, Texas and Corvallis, Oregon) for proportion of dormant seed, visual pod dehiscence scores, and two dehiscence surrogate measures (force to dehiscence and pod spiraling score).Trait performance varied between sites, but reliability (related to heritability) across sites was strong (dormant seed proportion: 0.68; dehiscence score: 0.61; spiraling score: 0.42; force to dehiscence: 0.41). A major locus controlling seed dormancy was found (q-value: 1.29 x 10 -5 ; Chromosome 1: Position: 63611165), which can be used by breeding programs to rapidly reduce dormancy in breeding populations. No significant dehiscence score QTL were found, primarily due to the high dehiscence rates in Corvallis, Oregon. Since Oregon is a potentially major V. villosa seed production region, further dehiscence resistance screening is necessary.